The relationship of self-congruity and attitude towards luxury brand - Sri, Hartini (Opción, 2019)
This research aims to explain the relation of self-congruity and attitudes towards the luxury brand and fashionable lifestyle as the moderation variable. The self-congruity divides into actual, ideal and social self -image. The brand attitude divides into cognitive, affective and conative. The sampling technique uses accidental sampling. The results of the study show that the ideal and social self-congruity does not affect the cognitive and affective attitudes shown by the sample. The fashionable lifestyle does not moderate the relationship between ideal self-congruence and conative attitude. In conclusion, fashionable lifestyle does not moderate the effect of ideal self-congruence on attitudes.